Nitric acid in cirrus clouds - Voigt, C.; Schlager, H.; Ziereis, H.; Kärcher, B.; Luo, B.P.; Schiller, C.; Krämer, M.; Popp, P.J.; Irie, H.; Kondo, Y. (Geophysical Research Letters, 2006)
Uptake of nitric acid (HNO 3 ) in Arctic cirrus ice crystals was observed on 11 February 2003 by in-situ instruments onboard the M55 Geophysica aircraft. The cirrus cloud with a mean ice water content of 5.4 mg m -3 covered northern Scandinavia for several hours and extended up to the thermal tropopause at 12.3 km. Within the cirrus region, on average 9% of the total HNO 3 measured as reactive nitrogen (NOy) is present in ice particles, increasing to 19% at temperatures below 205 K. In contrast to previous studies, we discuss the HNO 3 uptake in ice in terms of HNO 3 /H 2 O molar ratios in ice crystals. The HNO 3 content of the ice increases with increasing gas phase HNO 3 concentrations and decreasing temperatures. Enhanced uptake of HNO 3 in ice and heterogeneous chemistry on cold cirrus clouds may disturb the upper tropospheric ozone budget.